ANALISIS KEPUTUSAN PEMBELIAN PRODUK SCARLETTWHITENING PADA MAHASISWA DI JAKARTA - Adinda Kenya Nasyaya Denris (2022)
Competition in the business world looks increasingly tight, as well as the cosmetic industry. The high demand for cosmetic needs has forced businesses to carry out various appropriate marketing strategies to make purchasing decisions for the products offered. This study aims to analyze whether there is influence of brand ambassadors, electronic word of mouth, and brand image on purchasing decisions for local Scarlett Whitening products. The population in this study were students in Jakarta using a purposive sampling method and collected 100 respondents using Scarlett Whitening. The research was processed with the help of SmartPLS 3.0 software and the results were (1) Brand ambassador has a positive and insignificant effect with a coefficient of 0.115 on purchasing decisions, (2) E-Wom has a positive and significant effect with a coefficient value of 0.650 on brand image, (3) Brand image has a positive and significant effect with a coefficient value of 0.255 on decisions purchasing decisions, (4) Brand ambassadors have a direct positive and significant effect with a coefficient of 0.359 on purchasing decisions, (5) E-wom has a direct positive and significant effect with a coefficient of 0.337 on purchasing decisions, (6) Brand ambassadors have a positive and not significant effect indirectly with a path coefficient result value of 0.029 on purchasing decisions, and (7) E-wom has a positive and significant effect with a path coefficient result value of 0.165 on purchasing decisions indirectly. The joint contribution of brand ambassadors and e-woms to brand image is 54.8%, brand ambassadors and e-wom and brand image to purchasing decisions is 72.2% and the remaining 27.8% is influenced by other variables outside the model this research.